The Oxford handbook of the use of force in international law - Weller, M. (Marc); Solomou, Alexia; Rylatt, Jake William (Oxford handbooks, 2015)
This Oxford Handbook provides an authoritative and comprehensive analysis of one of the most controversial areas of international law. Over sixth contributors assess the current state of the international law prohibiting the use of force, assessing its development and analysing the many recent controversies that have arisen in this field